KESESUAIAN BATUBARA LAPISAN D UNTUK PROSES GASIFIKASI BAWAH PERMUKAAN - Salinita, Silti; Purnama, Asep Bahtiar; Yuniardi, Yuyun; Nurdrajat; Sendjaja, Yoga A. (Jurnal Teknologi Mineral dan Batubara, 2024)
Coal seam D is part of the Suban Burung Block, Muara Enim Formation, Central Palembang Subbasin, South Sumatra Basin, and is dated to the Middle to Late Miocene. The aims of this study is to determine the suitability of coal characteristics for (UCG) technology. The research was conducted on coal samples from seam D obtained from drilling during Underground Coal Gasification activities that utilized using the maceral composition method for coal utilization. Several coal quality parameter were tested, including calorific value, vitrinite reflectance, total sulfur content, ash content, total moisture content, ash fusion temperature, alkali oxide content (Na₂O + K₂O), maceral composition (vitrinite, liptinite, and inertinite), volatile matter content, as well as carbon and hydrogen content. Additionaly, to assess its applicability for UCG, the parameters of coal seam thickness and depth were also considered. The study results indicate that the characteristics of coal seam D has suitable for normative combustion and gasification using a fixed bed gasifier, a process similar to underground coal gasification. The thickness and depth of coal seam D are suitable for the application of Underground Coal Gasification (UCG) technology.